2018
DOI: 10.17696/2318-3691.25.3.2018.1265
|View full text |Cite
|
Sign up to set email alerts
|

Nanopartículas de prata biossintetizadas por Mikania glomerata Sprengel inibem o crescimento de Candida albicans e Staphylococcus aureus

Abstract: Introduction:In recent years there has been an increase in cases related to infection by Candida spp. and Staphylococcus spp., as well as the appearance of strains resistant to conventional antibiotics. Nanoparticle biosynthesis consists of the reduction of a metal ion by compounds of natural origin as secondary metabolites of plants and organisms, being the most indicated form because it presents less toxicity when compared to the chemical synthesis. In this way, the biological synthesis is an alternative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Regarding the antifungal activity, the nanoparticles showed superior efficacy in relation to the extract, being equally effective against C. albicans and C. glabrata , whereas the extract had no effect against C. glabrata . Similar results were obtained by Kischkel et al., who reported that silver nanoparticles biosynthesized from the leaf extract of Mikania glomerata Sprengel exhibited antifungal effect, whereas the extract was inactive 65 . According to Dutta et al., silver nanoparticles cause damage to the membrane and fungal wall, increasing the permeability of nanoparticles, leading to an increase in ROS and extravasation of intracellular components 66 …”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Regarding the antifungal activity, the nanoparticles showed superior efficacy in relation to the extract, being equally effective against C. albicans and C. glabrata , whereas the extract had no effect against C. glabrata . Similar results were obtained by Kischkel et al., who reported that silver nanoparticles biosynthesized from the leaf extract of Mikania glomerata Sprengel exhibited antifungal effect, whereas the extract was inactive 65 . According to Dutta et al., silver nanoparticles cause damage to the membrane and fungal wall, increasing the permeability of nanoparticles, leading to an increase in ROS and extravasation of intracellular components 66 …”
Section: Resultssupporting
confidence: 75%
“…Similar results were obtained by Kischkel et al, who reported that silver nanoparticles biosynthesized from the leaf extract of Mikania glomerata Sprengel exhibited antifungal effect, whereas the extract was inactive. 65…”
Section: Evaluation Of Antimicrobial Activitymentioning
confidence: 99%